Prototipe Kelas Pintar dengan Absensi Otomatis MAC Address Gawai Berbasis IoT - Adi Setiawan; Gyga Putra Parsaulian Hutauruk; Tita Aisyah (Yayasan Literasi Sains Indonesia, 2023)
This IoT-based smart classroom prototype was built using the NodeMCU microcontroller ESP8266. The automation system works by checking if there are users connected to the access point in the classroom and the course scheduled to use it. The attendance check is done by fetching MAC address from a user's device automatically. Next, it will activate relay to turn on electrical facilities in the used classroom, such as lamps, fans, or air conditioners. The system also uses the website using MySQL database to monitor classroom conditions, edit class schedules, register user devices to the system and access attendance data. From the tests carried out, the system can run according to design. Among other things, the relay circuit can be arranged according to the schedule of activities and the whereabouts of the user. Attendance data can be displayed according to users who are connected and registered in the system. The calculations on total delay of system yield results that the delay to activate the classroom is 10.66 ± 0.87 seconds on the website and 14.55 ± 0.78 seconds on the relay. On the other hand, the delay needed to deactivate the classroom is 39.34 ± 3.69 seconds on the website and 36.26 ± 3.70 seconds on the relay.